Cell contacts orient some cell division axes in the Caenorhabditis elegans embryo (The Rockefeller University Press, 1995)
Cells of the early Caenorhabditis elegans embryo divide in an invariant pattern. Here I show that the division axes of some early cells (EMS and E) are controlled by specific cell-cell contacts (EMS-P2 or E-P3 contact). Altering the orientation of contact between these cells alters the axis along which the mitotic spindle is established, and hence the orientation of cell division. Contact-dependent mitotic spindle orientation appears to work by establishing a site of the type described by Hyman and White (1987. J. Cell Biol. 105:2123-2135) in the cortex of the responding cell: one centrosome moves toward the site of cell-cell contact during centrosome rotation in both intact embryos and reoriented cell pairs. The effect is especially apparent when two donor cells are placed on one side of the responding cell: both centrosomes are "captured," pulling the nucleus to one side of the cell. No centrosome rotation occurs in the absence of cell-cell contact, nor in nocodazole-treated cell pairs. The results suggest that some of the cortical sites described by Hyman and White are established cell autonomously (in P1, P2, and P3), and some are established by cell-cell contact (in EMS and E). Additional evidence presented here suggests that in the EMS cell, contact-dependent spindle orientation ensures a cleavage plane that will partition developmental information, received by induction, to one of EMS's daughter cells.